Spiritual Marketplace : Baby Boomers and the Remaking of American Religion - Roof, Wade Clark (Book collections on Project MUSE., 1999)
In large chain bookstores the ""religion"" section is gone and in its place is an expanding number of topics including angels, Sufism, journey, recovery, meditation, magic, inspiration, Judaica, astrology, gurus, Bible, prophesy, evangelicalism, Mary, Buddhism, Catholicism, and esoterica. As Wade Clark Roof notes, such changes over the last two decades reflect a shift away from religion as traditionally understood to more diverse and creative approaches. But what does this splintering of the religious perspective say about Americans? Have we become more interested in spiritual concerns or h.